A quantity study of marital satisfaction, romantic jealousy and female's aggression (psychological and physical) - Edalati, Ali; Redzuan, Ma'rof (Medwell Journals, 2010)
The objective of this study is to determine the relationship among marital satisfaction, romantic jealousy and female’s aggression (physical and psychological). The women who participated in this study were those already registered as aggressive women in the counselling clinics. All of the 337 wives who were included in this study suffered from level of physical and psychological aggression were selected randomly for this investigation. Physical and psychological aggression were measured through Conflict Tactics Scale (CTS). The Spearman’s Rho for Rank Order Correlation test was used to determine the relationship among marital satisfaction, romantic jealousy and physical aggression. The test showed a positive relationship between jealousy and women’s physical aggression and a negative relationship between marital satisfaction and women’s physical aggression. The Pearson’s Product-Moment Correlation Test was utilized to determine the relationship among jealousy, marital satisfaction and psychological aggression. It showed a positive relationship between jealousy and women’s psychological aggression. Also there was a negative relationship between marital satisfaction and women’s psychological aggression. The Multivariate Regression Analysis was used to answer the last objective. The analysis showed that from the two predictor variables such as marital satisfaction and romantic jealousy, were found to be significant in explaining the observed variation in psychological aggression (DV). Generally, the final model has explained 21.5% of total observed variance in psychological aggression.